Indicators of the Banking System and Prospects of Credit Processes in the Management of the Country’s Credit Rating - GAVKHAR, KHAMDAMOVA; MAKHFURAT, EGAMOVA; MURODOVA, DILNOZA; SHAKHLO, DAVIROVA; NARGIZA, MADJIDOVA (The journal of contemporary issues in business and government, 2021)
Reforms in the formation of a stable and effective economy in our country are now demonstrating their results. In particular, significant progress has been made in the implementation of deep structural changes in the economy, strengthening the growth of incomes, efficient foreign trade and investment processes, stable development of the banking and financial system. At present, the socio-economic development of the world is drastically different from the previous stages in terms of probation. In this case, the main and important aspects are intensifying the integration and globalization of national economies. This article discusses the banking system infrastructure, in particular, the theoretical infrastructure of the bank infrastructure, its elements, its characteristics and procedures for establishing. There are also problems with the formation and development of the banking infrastructure in the country and provides practical proposals for their elimination.